Merancang Aplikasi Catatan Keuangan (Tabungan) Di Masjid Ar-Rahman Lamahu Berbasis Web - Muhammad Fauzi Dhuhuri; Farid F (Journal Of Software Engineering And Communication, 2026)
The Ar-Rahman Mosque which is located near South Huntu village, in South Bulango district, and operates like a regular mosque. The mosque is a place that functions to carry out prayers for Muslims. The community carries out many activities at the Ar-Rahman Lamahu Mosque, including sacrificial activities. Every year when sacrificial activities are carried out, savings records are still done manually using physical books which look non-transparent and untidy. After solving this problem, the author began to build a web-based financial records (savings) application for qurban activities. This application was built using the Laravel Framework and support MySQL basisdata. The design of this system runs well and helps in processing data and preparing member financial (savings) reports.